Utilization of Therapeutic Hypothermia and Neurological Injury in Neonates with Mild Hypoxic-Ischemic Encephalopathy: A Report from Children's Hospital Neonatal Consortium - Rao, Rakesh; Mietzsch, Ulrike; DiGeronimo, Robert; Hamrick, Shannon E.; Dizon, Maria L. V.; Lee, Kyong-Soon; Natarajan, Girija; Yanowitz, Toby D.; Peeples, Eric S.; Flibotte, John; Wu, Tai-Wei; Zaniletti, Isabella; Mathur, Amit M.; Massaro, An (American Journal of Perinatology, 2020)
Objective This study was aimed to describe utilization of therapeutic hypothermia (TH) in neonates presenting with mild hypoxic-ischemic encephalopathy (HIE) and associated neurological injury on magnetic resonance imaging (MRI) scans in these infants.Study Design Neonates ≥ 36 weeks' gestation with mild HIE and available MRI scans were identified. Mild HIE status was assigned to hyper alert infants with an exaggerated response to arousal and mild HIE as the highest grade of encephalopathy recorded. MRI scans were dichotomized as “injury” versus “no injury.”Results A total of 94.5% (257/272) neonates with mild HIE, referred for evaluation, received TH. MRI injury occurred in 38.2% (104/272) neonates and affected predominantly the white matter (49.0%, n = 51). Injury to the deep nuclear gray matter was identified in (10.1%) 20 infants, and to the cortex in 13.4% (n = 14 infants). In regression analyses (odds ratio [OR]; 95% confidence interval [CI]), history of fetal distress (OR = 0.52; 95% CI: 0.28–0.99) and delivery by caesarian section (OR = 0.54; 95% CI: 0.31–0.92) were associated with lower odds, whereas medical comorbidities during and after cooling were associated with higher odds of brain injury (OR = 2.31; 95% CI: 1.37–3.89).Conclusion Majority of neonates with mild HIE referred for evaluation are being treated with TH. Odds of neurological injury are over two-fold higher in those with comorbidities during and after cooling. Brain injury predominantly involved the white matter.Key Points
Keywords: therapeutic hypothermia; white matter injury; mild hypoxic-ischemic encephalopathy; MRI; EEG